The Effects of Marketing Communications on Malaysia's Consumer Based Brand Equity and Intention to Visit Among Potential Tourists from Gulf Countries: The Case of Jeddah and Dubai - Alfandi, Ashraf Mohammad Teehi (2011)
It has been long recognized that marketing communications (MC) are important activities that influencing potential tourist's attitude and behavior toward tourism destinations. However, factors such as tourism service intangibility, globalization, increasing advertising expenditure, fierce competition as well as upcoming tourism destinations competing for the same market put much more emphasize on the need for better MC practice and effectiveness. With this in mind, this study argues in favor of assessing the communication effects rather than sales-based effects of MC (as often used by destination marketers). More specifically, this study focuses on the long-term communication effects of MC activities by looking at MCs influence on the perceived destination Consumer Based Brand Equity (CBBE) dimensions (awareness, perceived quality and image) and the influence of these dimensions on the Intention to Visit (ItV) Malaysia among the Gulf Countries (GC) potential tourists. Data was collected using purposive sampling method in two major cities in the gulf area namely Dubai and Jeddah. A self administrated questionnaire was designed especially for the purpose of this study. 405 usable responses were collected and analyzed using a variety of statistical techniques from SPSS version 18. The findings indicated that both controlled and uncontrolled MCs have a significant effect on the three CBBE dimensions (awareness, perceived image and quality), however, uncontrolled MC is found to have a greater influence compare to controlled MC on these dimensions. Additionally, the perceived CBBE dimensions are found to predict ItV. Nevertheless, perceived destination image is found to have the greater influence on the potential tourist's ItV. The findings also revealed that potential tourists from GC did not hold either an extreme positive or negative destination image attributes about Malaysia. Based on the study findings, it is recommended that destination marketers therefore focus on more narrow set of destination image attributes in order to avoid having confused image from the potential consumer point of view. It is also recommended that destination marketers use multiple sources of information to target tourists. In particular, the uncontrolled MC namely WOM seems to be the highest incidence of information source. Theoretically, the study contributes to the body knowledge by providing empirical evidence to support theories and previous literature related to measuring MCs effectiveness and tourism destination brand equity as well as the relationship between destination Brand equity dimensions and the ItV. Further, this study filled the gap in the literature by providing a theoretical framework assessing the effectiveness of MCs especially in the long term. Methodologically, the study contributes by providing a measurement scale for CBBE dimensions of tourism destination attributes based on previous literature and used in this study. Furthermore, factor analysis had identified new attributes with regards to perceived destination image and quality. However, the study's sampling limitations should admittedly be considered in weighing the significance of all these contributions.